Nanogenerators: Highly‐Efficient, Flexible Piezoelectric PZT Thin Film Nanogenerator on Plastic Substrates (Adv. Mater. 16/2014). (April 2014) - Park, Kwi‐Il; Son, Jung Hwan; Hwang, Geon‐Tae; Jeong, Chang Kyu; Ryu, Jungho; Koo, Min; Choi, Insung; Lee, Seung Hyun; Byun, Myunghwan; Wang, Zhong Lin; Lee, Keon Jae
<x xml:space="preserve">Abstract</x> A highly‐efficient, lightweight, flexible, piezoelectric lead zirconate titanate (PZT) thin‐film nanogenerator is demonstrated by employing the laser lift‐off transfer technique and a lateral electrode structure. As reported by K. J. Lee and co‐workers on page 2514, this large‐area PZT thin‐film nanogenerator can convert to the highest output performance from a slight mechanical deformation and provides the feasibility of fully flexible self‐powered electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>